2022
DOI: 10.3390/medicina58020245
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Levels in Parkinson’s Disease: A Cross-Sectional Electronic Medical Record Database Study from a Tertiary Referral Centre in Romania

Abstract: Background and Objectives: Parkinson’s disease (PD) is a prevalent neurodegenerative condition responsible for progressive motor and non-motor symptoms. Currently, no prophylactic or disease-modifying interventions are available. Uric acid (UA) is a potent endogenous antioxidant, resulting from purine metabolism. It is responsible for about half of the antioxidant capacity of the plasma. Increasing evidence suggests that lower serum UA levels are associated with an increased risk of developing PD and with fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 64 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…Postmortem tissue studies have shown low urate levels in the substantia nigra in patients with PD. In animal models, UA has a neuroprotective effect on dopaminergic neurons due to the modulation of neuroinflammation and oxidative stress [31]. Based on our results, it can be assumed that in PD, an increase in hypoxanthine levels indicates a decrease in its conversion to UA efficiency.…”
Section: Resultssupporting
confidence: 55%
“…Postmortem tissue studies have shown low urate levels in the substantia nigra in patients with PD. In animal models, UA has a neuroprotective effect on dopaminergic neurons due to the modulation of neuroinflammation and oxidative stress [31]. Based on our results, it can be assumed that in PD, an increase in hypoxanthine levels indicates a decrease in its conversion to UA efficiency.…”
Section: Resultssupporting
confidence: 55%
“…The reason behind this divergence in literature could possibly arise from the inclusion of PD patients at variable stages of the disease. In early-stage PD, lower serum UA could be an indicator of an endogenic capacity to cope with PD-related cerebral oxidative stress induced by multiple neuropathological factors, such as protein misfolding, mitochondrial dysfunction, excitotoxicity, etc., 29,30 . Thus, decreased UA serum concentrations in early PD patients could re ect an e cient mobilization of peripheral antioxidant resources to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has also been observed in post-traumatic brain injury studies showing that decreased UA serum levels concurred with increased UA concentrations in damaged brain tissues 28 . With time however, the body's natural defenses seem to become insu cient, moreso given decreased UA production as the disease progresses, coupled by its excessive consumption in PD 23,29 . Thus, at more advanced stages of PD, patients maintaining higher concentrations of serum UA might be more advantaged compared to patients exhibiting de cit levels of UA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations